2020
DOI: 10.1186/s43044-020-00066-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient adherence to antihypertensive medications in upper Egypt: a cross-sectional study

Abstract: Background: Control of hypertension is a very difficult issue. Non-adherence to medications is a well-recognized factor contributing to uncontrolled hypertension. It is required to detect factors that affect adherence of patients to antihypertensive medications at different societies and good planning with the collaboration of governments, universities, media, pharmaceutical companies, and civil society to create intervention programs ensuring good adherence to medications. In our study, we aimed to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
6
18
1
Order By: Relevance
“…However, this finding is lower than a study reported from America in 2015 (69%) [ 63 ] and Korea (81.7%) [ 64 ]. In contrast, this finding is higher than a study reported from Egypt (46.12%) [ 65 ] and Palestine (45.8%) [ 66 ]. The discrepancy might be due to differences in the socioeconomic status of participants.…”
Section: Discussioncontrasting
confidence: 81%
“…However, this finding is lower than a study reported from America in 2015 (69%) [ 63 ] and Korea (81.7%) [ 64 ]. In contrast, this finding is higher than a study reported from Egypt (46.12%) [ 65 ] and Palestine (45.8%) [ 66 ]. The discrepancy might be due to differences in the socioeconomic status of participants.…”
Section: Discussioncontrasting
confidence: 81%
“…Our study also showed that physicians felt that fear of side effects from long term medication use contributed to patient non-adherence to antihypertensive medications. Age, gender, place of residence, income, educational levels, number of prescriptions, price of medications, comorbidities, adverse effects, and not feeling the need for regular use have shown to be predictors of adherence to antihypertensive medications in studies conducted in Egypt, Pakistan, and Bangladesh [ 17 , 18 , 45 ]. Travel costs, long wait times, clinic operating hours, inadequate patient knowledge, and under-dispensing of medications were shown to be other limiting factors in a study in Nigeria [ 34 ], which were also mentioned by participants in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Travel costs, long wait times, clinic operating hours, inadequate patient knowledge, and under-dispensing of medications were shown to be other limiting factors in a study in Nigeria [ 34 ], which were also mentioned by participants in our study. Predictors of antihypertensive medication include age, gender, place of residence, income, educational levels, number of prescriptions, price of medications, comorbidities, adverse effects, and not feeling the need for regular use [ 17 , 18 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers of not complying with antihypertensive medication were determined. The reasons were; stopping medication due to cost of the medications 20 , 34 , fear of the side effect 35 , 36 , feeling well (asymptomatic) 37 , avoiding addiction to drugs 38 , 39 and use of traditional medicine. 28 …”
Section: Discussionmentioning
confidence: 99%